Implementasi Unit Testing menggunakan metode Test-First Development - Rizkyana, Muhamamd Agung; Yunanto, Yunanto; Yoga, Yoga; Widianto, Septian Rheno (MULTINETICS, 2021)
Today we are faced with a disruption era that brought some challenges for any business field, especially the software development field. Software development should be adaptive to those challenges. One of the most used and implemented for today in software development lifecycle was Agile. Agile Methodology can push out the software to be released. Meanwhile, the release velocity was not enough to keep the software accepted and used by users. The quality of the software was necessary because the alignment belongs to user needs showing those qualities. One of the methods in Agile that assuring the quality was Test-Driven Development (TDD). TDD has various techniques. This research used Test-First Development (TFD). TFD technique used for guidance unit testing of data service application with REST API architecture. The objective was to show TDD implementation that aligns with the concept and theory for the case study.